The molecular basis for the development of neural maps. (December 2013) - Wei, Yi; Tsigankov, Dmitry; Koulakov, Alexei
Abstract : Neural development leads to the establishment of precise connectivity in the nervous system. By contrasting the information capacities of cortical connectivity and the genome, we suggest that simplifying rules are necessary in order to create cortical connections from the limited set of instructions contained in the genome. One of these rules may be employed by the visual system, where connections are formed on the basis of the interplay of molecular gradients and activity‐dependent synaptic plasticity. We show how a simple model that accounts for such interplay can create both neural topographic maps and more complex patterns of ocular dominance, that is, the segregated binary mixture of projections from two eyes converging in the same visual area. With regard to the ocular dominance patterns, we show that pattern orientation may be instructed by the direction of the gradients of molecular labels. We also show that the periodicity of ocular dominance patterns may result from the interplay of the effects of molecular gradients and correlated neural activity. Overall, we propose that simple mechanisms can account for the formation of apparently complex features of neuronal connections.